IN VITRO STUDY OF LYMPHOTROPIC AND IMMUNOMODULATORY PROPERTIES OF THE PESTE DES PETITS RUMINANTS VIRUS (PPRV) - Z. A. Nizamani a; R. Servan de Almeida b; E. Albinab; F. Parveena; G. Libeau b (Journal of Animal and Plant Sciences, 2014)
The Peste des petits ruminants (PPR) is a viral disease which affects sheep and goats and even the wild ruminants. About a billion small ruminants are found in the PPR enzootic areas. Morbilliviruses are primarily lymphotropic and secondarily epitheliotropic. Viral infection and interaction of viral proteins with lymphatic tissues are partly responsible for immune suppression. Transient immunosuppression is also observed after vaccination with attenuated vaccines. Viral isolation is traditionally done on Vero but newer recombinant cell lines are also used. In this work, sensitivity of three cell lines i.e. SLAM-ve-Vero, Vero.DogSLAMtag and B95a having Marmoset SLAM have been compared for PPRV titration. Moreover, infectivity of phytohemagglutinin (PHA) stimulated peripheral blood mononuclear cells (PBMCs) with PPR virus (PPRV) has been tested. Finally, live PPRV, recombinant nucleoprotein of PPR Virus (NPPRV) and truncated ∆420-525 NPPRV have been used to demonstrate in vitro inhibition of PHA stimulated lymphoproliferation of PBMCs of naïve goats. The presence of canine SLAM (Signaling lymphocyte activation molecule) receptor but not the marmoset SLAM, enhances infectivity of cell lines by up to 0.8 log10. At multiplicity of infection (MOI) of 0.1, 83.6 percent of PBMCs can be infected with PPRV. PPRV could completely inhibit lymphoproliferation at MOI of 0.75 while NPPRV and ∆420-525 NPPRV could suppress lymphoproliferation by 7.4 % and 17.6 %, respectively. PPRV is lymphotropic as PPRV (Nigeria 75/1) is capable of infecting mitogen activated PBMCs and that presence of canine SLAM in Vero cell line greatly enhances infectivity of PPRV as compared to SLAM negative Vero. Vero.DogSLAMtag is more sensitive cell line for PPRV titration and PPRV isolation. PPRV (Nigeria 75/1) and recombinant N-proteins induce in vitro inhibition of cell proliferation of mitogen stimulated PBMCs of naive goats. Using deleted mutant of NPPRV expressed in baculovirus system, amino acid sequence of NPPRV between 1-420 was found responsible for inducing immune suppression.
Keywords: Immunomodulation; Immune suppression; lymphoproliferation; Nucleoprotein; SLAM; Morbillivirus; PPRV